PISA PROBLEM SOLVING: THE INVESTIGATION OF STUDENT'S EXPERIENCE THROUGH DISTANCE LEARNING DURING PANDEMIC - Sapto Aji Nugroho; Christina Kartika Sari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Problems similar to PISA with the theme of hollow iron are used as a helping instrument to see how students' problem solving abilities are. In accordance with the PISA research, the subjects of this study were 8th graders of junior high school in Karanganyar Regency, Indonesia with an age range of 15-16 years. In addition to tests, other auxiliary instruments are interview guidelines where the data obtained from the two instruments are compared so that the data obtained are truly valid. Subjects were selected by means of snowball sampling until the data obtained were considered sufficient by the key instrument, namely the researcher himself. Through data collection, data reduction, data presentation, conclusion drawing and verification, the results show that students with high abilities can identify problems well, formulate a settlement plan with simple procedures, execute plans in a coherent and clear manner, and re-examine the components involved. considered dubious. Students with moderate abilities tend not to be careful in identifying information which results in discrepancies in the answers obtained. while students with low abilities find it difficult to solve non-routine problems and tend not to try to think of better solutions.